2020
DOI: 10.1002/alr.22653
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose and long‐term azithromycin significantly decreases Staphylococcus aureus in the microbiome of refractory CRS patients

Abstract: Background The sinonasal microbiome is believed to play an important role in the pathophysiology of refractory chronic rhinosinusitis CRS We evaluated changes in the microbiome following a-month course of low-dose azithromycin Assessing microbiome alterations following such a treatment may help identify underlying mechanisms of this drug Methods A total of adults with refractory CRS were enrolled in a double-blind randomized placebo-controlled trial Patients were randomized to mg of azithromycin or placebo tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…6 The benefit of adding AZI, and its capacity to influence S aureus clearance, is demonstrated clinically in this study, whereas our group also previously showed that the mechanism behind this effect may be associated with the CRS epithelium healing properties AZI has through its rho‐kinase inhibitor‐like properties, even in the presence of S aureus . 7 Furthermore, we recently reported with an in‐depth 16S rRNA microbiome analysis that patients on a low‐dose AZI regimen showed a significant decrease in the abundance of sinonasal S aureus variants, whereas patients on placebo instead showed a decrease in key species regulating a healthy sinonasal microbiome, such as Bacteroides vulgatus and Lachnospiraceae spp, resulting in a significant decrease in microbial diversity, which may in part be responsible for disease persistence. 24 Overall, we can postulate that AZI's antibacterial, anti‐inflammatory, and immunomodulating characteristics play a major role in clearing key virulent sinonasal pathogens when given at a low dose and over the long term, providing an improved barrier and modified ecological niche.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The benefit of adding AZI, and its capacity to influence S aureus clearance, is demonstrated clinically in this study, whereas our group also previously showed that the mechanism behind this effect may be associated with the CRS epithelium healing properties AZI has through its rho‐kinase inhibitor‐like properties, even in the presence of S aureus . 7 Furthermore, we recently reported with an in‐depth 16S rRNA microbiome analysis that patients on a low‐dose AZI regimen showed a significant decrease in the abundance of sinonasal S aureus variants, whereas patients on placebo instead showed a decrease in key species regulating a healthy sinonasal microbiome, such as Bacteroides vulgatus and Lachnospiraceae spp, resulting in a significant decrease in microbial diversity, which may in part be responsible for disease persistence. 24 Overall, we can postulate that AZI's antibacterial, anti‐inflammatory, and immunomodulating characteristics play a major role in clearing key virulent sinonasal pathogens when given at a low dose and over the long term, providing an improved barrier and modified ecological niche.…”
Section: Discussionmentioning
confidence: 99%
“…Anaerobic bacteria isolation was performed on a Brucella agar with 5% sheep blood and in an anaerobe broth (Schaedler Anaerobe Broth; Oxoid). A second culture swab was also performed and stored for 16S ribosomal RNA microbiome analyses. 24 …”
Section: Methodsmentioning
confidence: 99%
“…For example, the presence of Staphylococcus aureus in the sinonasal microbiome appears to predict failure of endoscopic sinus surgery in patients with CRS at high risk of recurrence ( 22 ). Identification of such microorganisms, then allows for clinical trials that measure the effectiveness of specific antibiotic regimens in reducing the abundance of harmful pathogens in patients with refractory disease such as CRS ( 23 ).…”
Section: Microbiome Research: An Overviewmentioning
confidence: 99%
“…41,42 In addition, as mentioned above, there is no consensus on whether to recommend macrolide antibiotics after nasal endoscopic surgery, 2,12,28 and in eligible studies, the efficacy of macrolide on CRS patients after ESS is a topic of great contradictions and controversies. 20,21,[24][25][26][27]34,35 As the present microbial environment is increasingly resistant, retrieving, organizing, summarizing, and analyzing the latest evidence of macrolides in the treatment of patients The clinical heterogeneity caused by certain differences in patient population, intervention outcome indicators of interest to researchers, medical ethics of the regions or countries where the studies were conducted, and so forth, often leads to inconsistent results between the studies. Based on the comprehensive results from the 4 comparisons in this study, especially the results from the first comparison, the evidence suggested that the use of macrolide after CRS surgery may not have significant effects on the improvement of patients' quality of life and disease severity, but may have a certain effect on the improvement of postoperative NES.…”
Section: Clinical Significancementioning
confidence: 99%